2015
DOI: 10.3389/fmicb.2015.00945
|View full text |Cite
|
Sign up to set email alerts
|

Legume-rhizobia signal exchange: promiscuity and environmental effects

Abstract: Although signal exchange between legumes and their rhizobia is among the best-known examples of this biological process, most of the more characterized data comes from just a few legume species and environmental stresses. Although a relative wealth of information is available for some model legumes and some of the major pulses such as soybean, little is known about tropical legumes. This relative disparity in current knowledge is also apparent in the research on the effects of environmental stress on signal ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 142 publications
(131 reference statements)
1
31
0
Order By: Relevance
“…Instead, an extensive signalling process 3537 between legumes and their rhizobial partners can impose a high degree of selectivity on the relationship 36, 38, 39 , although the degree of selectivity varies greatly among hosts 39 . There are two explanations for this selectivity that are commonly proposed and are not mutually exclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, an extensive signalling process 3537 between legumes and their rhizobial partners can impose a high degree of selectivity on the relationship 36, 38, 39 , although the degree of selectivity varies greatly among hosts 39 . There are two explanations for this selectivity that are commonly proposed and are not mutually exclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Checcucci et al ., ). This could reflect the existence of strong host control of the interaction through mechanisms like partner choice (Lira et al ., ) or sanctioning (Kiers et al ., ). However, partner choice is not perfect, as nodules often house ineffective bacteria, with recent evidence suggesting that, in some instances, nodules can be colonized by a range of non‐N‐fixing rhizobia or even nonrhizobial bacteria (Birnbaum et al ., ; Busby et al ., ; Checcucci et al ., ).…”
Section: Specificity and Effectiveness Of Legume–rhizobium Interactiomentioning
confidence: 99%
“…Checcucci et al, 2016). This could reflect the existence of strong host control of the interaction through mechanisms like partner choice (Lira et al, 2015) or sanctioning (Kiers et al, 2003). However, partner choice is not perfect, as nodules often house ineffective bacteria, with recent evidence suggesting that, in some instances, nodules can be colonized by a range of non-N-fixing rhizobia or even nonrhizobial bacteria ( The performance (yellow, high; blue, low) is visualized on the plane of coevolution (shared phylogenetic history between the invading legume and the rhizobia with which it interacts in the invasion range) and interaction specialization (ranging from interactions between specialist legumes and specialist rhizobia to those between generalist legumes and generalist rhizobia).…”
Section: Specificity and Effectiveness Of Legume-rhizobium Interamentioning
confidence: 99%
“…Several reports describe the chemical dialog between microbes, plants, and other organisms by the exchange of soluble compounds (Badri et al 2009;Lira Jr et al 2015;Song et al 2015a;Liu et al 2016). Most of the studies reporting mVOCs-mediated communication belowground focus on the uni-directional responses and only a few studies reported on bidirectional mVOCs-mediated interactions.…”
Section: Mvocs-mediated Dialogmentioning
confidence: 99%